Triage nurses’ perspectives about abuse of older people: a study in a hospital setting - Fatemeh Estebsari; Sima Ghorbanzadeh; Arezoo Sheikh Milani; Zahra Saboohi; Marzieh Latifi; Arezoo Shahsavari; Zahra Rahimi Khalifeh Kandi (BMC Nursing)
Abstract Background Abuse of older people is a major public health problem. Although nurses are recognized as playing a crucial role in responding to elder abuse, it tends to be under-recognized and under-reported in Iranian hospitals The present study aimed to measure the level of public and legal triage nurses’ knowledge, attitude, and practice toward abuse of older people. Methods This cross-sectional study was conducted on 400 nurses working in teaching hospitals, from May to October 2022. Data collection tools were background information questionnaires and questionnaires on nurses’ knowledge, attitudes, and practices regarding elder abuse. A convenient sampling method was used in this study. The link to the questionnaires was sent electronically through the nurses’ hospital groups on WhatsApp online software. The data collected were analyzed using SPSS version 18.0. Mean and standard deviation were used for nurses’ knowledge, attitude, and practice, and Pearson’s correlation was used for the relationship and correlation between nurses’ knowledge, attitude, and performance. Significance level 0.05 considered. Results The mean age of the participating nurses was 33.8 ± 5.21 years. Based on the results, the mean scores of nurses’ general knowledge were 5.59 ± 1.35, legal knowledge was 3.52 ± 1.79, attitude was 43.06 ± 6.57, and practice regarding elder abuse was 12.49 ± 5.57. results showed a direct and significant relationship between nurses’ general knowledge of elder abuse and knowledge of physical elder abuse (P < 0.001). A strong and significant direct relationship was also observed between nurses’ knowledge of elder neglect and financial elder abuse (P < 0.001). Conclusion Nurses’ general knowledge, attitude, and practice towards elder abuse were lower than the mean. Based on the significant relationship between knowledge and attitude with nurses’ performance in the area of elder abuse, it is recommended that quality educational content be included in continuing education programs for nurses. To achieve the goals of changing nurses’ behavior, it is suggested that nursing education programs and curricula include the issue of elder abuse, its diagnosis, and reporting. Trial registration Not applicable.